Heterostructured TiO2 Spheres with Tunable Interiors and Shells toward Improved Packing Density and Pseudocapacitive Sodium Storage. Issue 46 (30th September 2019) - Xu, Xin; Chen, Bo; Hu, Junping; Sun, Bowen; Liang, Xiaohui; Li, Nan; Yang, Shengyuan A.; Zhang, Hua; Huang, Wei; Yu, Ting
Abstract: Insertion‐type anode materials with beneficial micro‐ and nanostructures are proved to be promising for high‐performance electrochemical metal ion storage. In this work, heterostructured TiO2 shperes with tunable interiors and shells are controllably fabricated through newly proposed programs, resulting in enhanced pseudocapacitive response as well as favorable Na + storage kinetics and performances. In addition, reasonably designed nanosheets in the extrinsic shells are also able to reduce the excess space generated by hierarchical structure, thus improving the packing density of TiO2 shperes. Lastly, detailed density functional theory calculations with regard to sodium intercalation and diffusion in TiO2 crystal units are also employed, further proving the significance of the surface‐controlled pseudocapacitive Na + storage mechanism. The structure design strategies and experimental results demonstrated in this work are meaningful for electrode material preparation with high rate performance and volume energy density. Abstract : Heterostructured TiO2 spheres with tunable interiors and shells are controllably designed. Because of the improved pseudocapacitive response, TiO2 hollow spheres with smaller nanosheets display the best Na + storage properties. Besides, their increased packing density is also promising for high volume energy density devices.